Jiwa Kewirausahaan di Sektor Publik (Studi Kasus Kepemimpinan Walikota Tanjungpinang 2013-2014) - Pozlita, Pozlita; Muhammad, Adji Suradji; Yudiatmaja, Wayu Eko (Jurnal Ilmu Administrasi Negara (JUAN), 2014)
Bureaucracy Entrepreneurial in public is a requirement that is proven to have a positive impact in theleadership of Local Government for the welfare of the community by performing a variety of innovationsin order to survive and excel in competition in the era of regional autonomy. Tanjungpinang city is oneof the city located in the province of Riau islands which would require the soul of a local chief who hasthe spirit of change. figure of a Tanjungpinang Mayor 2013-2014 who considers that existingemployees are an asset in progress Tanjungpinang by noting that both retaining profitable assets. Thepurpose of this study is to describe and analyze the practice of application of the entrepreneurial spirit inthe leadership of Mayor Tanjungpinang 2013-2014. based on the exposure raises the issue of how theauthor seeks an entrepreneurial spirit that made by Mayor Tanjungpinang 2013-2014 as the latestbreakthroughs that are creative and innovative to developed Tanjungpinang superior and able tocompete with other cities. Informants in this study were derived from the government and communityleaders, the sampling technique used is purposive sampling technique that consists of 4 peopleinformant. The research method used was a qualitative research case study is a research approach thatdoes not try to look for relationships between variables as adopted by flow positivistic (quantitative), butrather to find meaning (symbols) with the natural way or with the testing procedure in detail againstthe background or a person subject or the storage area of the document or a particular event. Research isalready In the spirit of entrepreneurship to transform the public sector, that figure entrepreneurial spiritand character Tanjungpinang Mayor from 2013 to 2014 based on the self and perform a variety ofsharing with anyone related to the advancement of Tanjungpinang and there entrepreneurial spiritadopted by the leadership of Mayor Tanjungpinang 2013-2014. But still need improvement within thereform-promoting Tanjungpinang